All we had a novel - Weatherwax, Annie (Scribner, 2015)
For thirteen-year-old Ruthie Carmichael and her mother, Rita, life has never been stable. The only sure thing is their love for each other. Though Rita works more than one job, the pair teeters on the edge of poverty. When their landlord kicks them out, Rita resorts to her movie-star looks and produces carpet-installer Phil, "an instant boyfriend," who takes them in. Before long, Ruthie convinces her mother to leave and in their battered Ford Escort, they head East in search of a better life. When money runs out and their car breaks down, they find themselves stranded in a small town called Fat River where their luck finally takes a turn. Rita lands a steady job waitressing at Tiny's, the local diner. With enough money to pay their bills, they rent a house and Fat River becomes the first place they call home. Peter Pam, Tiny's transgender waitress and the novel's voice of warmth and reason, becomes Ruthie's closest friend. Arlene, the no-nonsense head waitress, takes Rita under her wing. The townspeople--Hank and Dotty Hanson, the elderly owners of the embattled local hardware store, and even their chatter-mouth neighbor Patti--become Ruthie and Rita's family. Into this quirky utopia comes smooth-talking mortgage broker Vick Ward, who entices Rita with a subprime loan. Why rent when you can own? Almost as soon as Rita buys a house their fortunes change. Faced once again with the prospect of homelessness, Rita reverts to survival mode, and the price she pays to keep them out of poverty changes their lives forever.
Originally published in hardcover in 2014
Includes a reading group guide
Keywords: Mothers and daughters / Fiction; Single mothers / Fiction; Teenage girls / Fiction; Poor / Fiction; Domestic fiction; Fiktionale Darstellung